Primary Retroperitoneal Masses: A Pictorial Essay - Abhishek Gupta; Alpana Manchanda; Sapna Singh; Rajdeep Singh; Nita Khurana; Aishwarya S. Durgad (Thieme Medical and Scientific Publishers Pvt. Ltd., 2024)
Primary retroperitoneal masses include a diverse and uncommon group of lesions that arise within the retroperitoneal space, but do not originate from any retroperitoneal organs. The majority of the lesions are malignant and imaging plays a pivotal role in the detection, staging, and preoperative planning. The evaluation of primary retroperitoneal masses is often challenging owing to the unfamiliarity with the common imaging features of various diseases affecting it. This article describes the multidetector computed tomography appearance of some primary retroperitoneal masses.